Cyberbullying - Kate Fogarty (EDIS)
“Bullying, or aggression on a continual basis between peers where one has a power advantage over another—is common among children and adolescents. Using intimidation and physical force or spreading rumors is often what comes to mind when we think of bullying. However, a form that parents and teachers may be less aware of is called “cyberbullying.” This involves put-downs, publicly sharing personal information, stalking, and other overt attacks upon a person, all using electronic communication.” This 2-page Family Album Radio transcript was written by Kate Fogarty and published by the UF Department of Family, Youth and Community Sciences, August 2012.